2022
DOI: 10.1136/ejhpharm-2021-003194
|View full text |Cite
|
Sign up to set email alerts
|

Developing a telepharmacy programme with home medication dispensing and informed delivery in a tertiary hospital: description of the model and analysis of the results

Abstract: ObjectivesThis study aimed to describe the actions taken to implement a telepharmacy programme with home medication dispensing and informed delivery in an outpatient pharmaceutical care unit of a tertiary hospital, where approximately 5000 patients are treated per year. It also aimed to substantiate the applicability and benefits of the programme through analysing the findings and measuring patient satisfaction.MethodsWe identified the operational, logistical, technological and legal needs, as well as the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…8,9 It has been also showed to reduce hospital admissions during the pandemic, diminish burden on hospitals, and save time to patients and staff. 4,10,11 Telepharmacy allows for a personalized interaction between the patient and the pharmacist to include patient-care services such as counseling, assessment of medication adherence, as well as comprehensive medication review. 2,8,12 Jordan, a developing Middle Eastern country, had a population of around 10.2 million in 2020, with an average age of 22.8 and a slightly higher male-to-female ratio.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 It has been also showed to reduce hospital admissions during the pandemic, diminish burden on hospitals, and save time to patients and staff. 4,10,11 Telepharmacy allows for a personalized interaction between the patient and the pharmacist to include patient-care services such as counseling, assessment of medication adherence, as well as comprehensive medication review. 2,8,12 Jordan, a developing Middle Eastern country, had a population of around 10.2 million in 2020, with an average age of 22.8 and a slightly higher male-to-female ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need for studies with a stronger methodological rigor to thoroughly address this regard. Despite the fact that the implementation of home delivery of medications is associated with several pros, such as treatment continuity, economic savings, decongestion of the healthcare centers, avoiding traveling expenses, saving patients' time, and enhancing the quality of life (10,17), there are potential drawbacks that should be highlighted. First, implementing a home drug delivery service without integrating it with the telepharmacy system, compromises the optimal provision of the pharmaceutical care (2).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that patients on maintenance medications through home delivery are more likely to take them as prescribed for conditions like diabetes, hypertension, and dyslipidemia ( 13 ). However, previous studies that investigated the benefits of home delivery services were self-administered questionnaires susceptible to social desirability bias ( 10 , 12 , 14 – 17 ). Therefore, there is a need for studies with a stronger methodological rigor to thoroughly address this regard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations